The role of growth hormone device optimization in patient-reported outcomes: real-world evidence from South Korea. (2nd January 2021) - Lee, Ji-Eun; Lee, Kee-Hyoung; Park, Mi Jung; Yang, Seung; Kim, Eun Young; Rhie, Young-Jun; Jung, Min-Ho; Yang, Aram; Kim, Shin-Hye; Chung, Lindsey Yoojin; Ko, Su Young; Lee, Young Ju; et al.
ABSTRACT: Background: Growth hormone (GH) treatment preference and adherence are affected by delivery device convenience, injection-site pain, confidence in correct dose administration, and device satisfaction. This survey investigated if switching device to NordiFlex® improved treatment experience in pediatric patients in South Korea. Design and methods: Patients aged 4–≤18 years were surveyed. Participants were NordiFlex® users who previously used NordiLet®/other devices. Participants compared preference, self-reported adherence, satisfaction, perceived ease of use, and device subjective benefits (across four domains: ease of use, self-efficacy, minimal disruption of daily life, positive feelings about injections ) of NordiFlex® vs. previous device. Results: Ninety-four patients were enrolled, of which 91.5% previously used NordiLet®. Significantly more patients preferred, and were more satisfied with NordiFlex® vs. previous device; mean score: 0.65 (95% confidence interval [CI]:0.41;0.88) and 0.61 (95% CI:0.36;0.85), respectively. Participants reported greater perceived ease of use (0.49 [95% CI:0.26;0.72]) and fewer missed injections (0.20 [95% CI:0.06;0.34], with NordiFlex® vs. previous device. Bivariate analysis showed significant associations between preference for NordiFlex® and higher scores on self-efficacy, ease of use, minimal disruption of daily life, and positive feelings about injection (all p < 0.001). Conclusion: These results suggest that improvements in device features could be associated with improved treatment experience.